2020
DOI: 10.1002/chem.202002320
|View full text |Cite
|
Sign up to set email alerts
|

Minisci C−H Alkylation of Heteroarenes Enabled by Dual Photoredox/Bromide Catalysis in Micellar Solutions**

Abstract: Aromatic heterocycles are omnipresent structural motifs in various natural products, pharmaceuticals and agrochemicals. This work describes ap hotocatalytic Miniscitype CÀHf unctionalization of heteroarenes with non-activated alkyl bromides. The reaction avoids stoichiometricr adical-promoters, oxidants, or acids, and is conducted using blue LEDs as the light source.T he reactive carbon-centered alkyl radicals are generated by merging the photoredox approachw ith bromidea nion co-catalysis and spatialp re-aggr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 68 publications
0
23
0
Order By: Relevance
“…[2][3][4][5][6][7] In this context, an impressive range of both photochemical and photocatalyzed processes has been investigated under micellar conditions including, among the most recent examples, photo-Fries rearrangements, [8,9] decarboxylation of αarylpropionic esters [10] and photoredox catalyzed processes. [11][12][13][14][15][16] A significant attention has been also given to the use of photocyclizations as reaction model to investigate micellar systems, as an example, the conversion of 2-pyridylphenyl ketone into fluorenone-like derivatives was investigated in sodium dodecyl sulfate and Triton X-100 micelles by Favaro and co-workers, via both steady-state and time-resolved analyses [17] More recently, Petrov and co-workers described the photochromism of 7,4'-Dihydroxyflavylium/trans-chalcone system in the presence of sodium bis(2-ethylhexyl) sulfosuccinate (AOT) as the surfactant. Interestingly, while cyclization of the chalcone derivative occurs at the hydrophobic side of the AOT reverse micelle interface, the generated flavylium ion move to the water pool, where the retro-cyclization slowly occurs.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7] In this context, an impressive range of both photochemical and photocatalyzed processes has been investigated under micellar conditions including, among the most recent examples, photo-Fries rearrangements, [8,9] decarboxylation of αarylpropionic esters [10] and photoredox catalyzed processes. [11][12][13][14][15][16] A significant attention has been also given to the use of photocyclizations as reaction model to investigate micellar systems, as an example, the conversion of 2-pyridylphenyl ketone into fluorenone-like derivatives was investigated in sodium dodecyl sulfate and Triton X-100 micelles by Favaro and co-workers, via both steady-state and time-resolved analyses [17] More recently, Petrov and co-workers described the photochromism of 7,4'-Dihydroxyflavylium/trans-chalcone system in the presence of sodium bis(2-ethylhexyl) sulfosuccinate (AOT) as the surfactant. Interestingly, while cyclization of the chalcone derivative occurs at the hydrophobic side of the AOT reverse micelle interface, the generated flavylium ion move to the water pool, where the retro-cyclization slowly occurs.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous reports, [19][20][21][22] as well as the work of others, [23][24][25][26][27] showed that micellar photocatalysis is an attractive tool for the activation of stable chemical bonds under mild reaction conditions. It can improve selectivity of processes and prolong the lifetimes of highly energetic intermediates by pre-organizing the components in the reaction mixture.…”
Section: Introductionmentioning
confidence: 94%
“…[17,18] We wished to achieve target reactivity through initial C-Cl activation followed by intramolecular 1,5 hydrogen-atom transfer (1,5-HAT). [19] Our previous reports, [29][30][31] as well as the work of others, [32][33][34][35][36] showed that micellar photocatalysis is an attractive tool for the activation of stable organic halides. It enables pre-organization of the components in the reaction mixture and provides high hydration energy of the released halide anions.…”
Section: Introductionmentioning
confidence: 95%